The Peculiarities of Nickname Structure in the Vicinity of Veliuona: Secondary Nicknames - Mickienė, Ilona; Baranauskienė, Rita (Respectus Philologicus, 2014)
The paper analyses 782 nicknames that were recorded at Veliuona vicinity during the project of the Institute of the Lithuanian Language “Modern Research of Geolinguistics in Lithuania: Optimisation of Network of Points and Interactive Spread of Dialectal Information”. The paper aims to identify the characteristic attributes of nickname structure. The analysis of the relations in derivation, i. e., tentatively distinguishing the derivation base and formant is the only way to talk about common word derivation. While researching the nicknames it is difficult to find such a universal criterion in derivation which would enable the distribution of nicknames into the primary and the secondary ones due to the fact that when a nickname and its appellative derivation motivation coincides the confusion arises. Thus, the paper invokes the structural analysis of nicknames to find universal criteria that would enable the distinction of nicknames into the primary and the secondary. The article eliminates the primary nicknames that do not differ from the motivational word, 241 secondary nickname is being researched ant structurally analysed. The structural analysis discloses a proper structure and common words being selected for nickname creation. Structurally analysing the secondary nicknames, the nicknames with suffix, inflection, mixed structure, compound, composite and phrasal nicknames were distinguished. It was determined that in vacinity of Veliuona the nicknames with suffix and inflection are mostly used.